2010
DOI: 10.5399/osu/jtrf.44.1.801
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Shared Operation of Commuter Rail Transit and Freight Railroads

Abstract: Seeking a thorough understanding of shared operation between commuter rail transit and freight railroads, a nationwide survey was conducted of transit and rail freight interaction. This survey contacted and received responses from all 21 commuter rail services in North America. In addition to a general understanding of the shared-use practices, this paper presents the key factors that contribute or impede successful shared-use operations between commuter rail and freight railroads by examining detailed operati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2012
2012

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…Commuter rail operates peak services with more widely spaced stations. Commuter rail trains can operate on the same rails as freight trains, provided that capacity exists along the corridors and agreements are established between the owners of the track and the local transit agency (21). Cabarrus County is directly connected to Uptown Charlotte by an existing Norfolk Southern freight rail line.…”
Section: Commuter Railmentioning
confidence: 99%
“…Commuter rail operates peak services with more widely spaced stations. Commuter rail trains can operate on the same rails as freight trains, provided that capacity exists along the corridors and agreements are established between the owners of the track and the local transit agency (21). Cabarrus County is directly connected to Uptown Charlotte by an existing Norfolk Southern freight rail line.…”
Section: Commuter Railmentioning
confidence: 99%
“…Another major issue to be addressed in the business model is how the transit service and the freight railroad share the maintenance cost. According to the findings of previous studies (8), quite a few transit operators identified allocation of the cost of the maintenanceof-way expense as the critical issue of joint operation, and some suggested that government should regulate the calculation of shared cost and shared use.…”
Section: Maintenance Responsibilitiesmentioning
confidence: 99%